THE UNFULFILLED GENDER STEREOTYPE IN LAMB TO THE SLAUGHTER BY ROALD DAHL - Anna Sriastuti; Elisabeth Ngestirosa Endang Woro Kasih (Linguistics and Literature Students' Journal, 2022)
As society is filled with diversity, such as differences in race, skin colour, culture, religion, andeconomy, it is common that each society has formed its own perception over things that happen around them. Stereotypes are among the most striking differences in perception. There may be perceptions regarding an unequal assessment of a community group based on attitudes and opinions, leading to wrong beliefs and losses for one party. Stereotypes are like masks put on individuals. Masks cover up individual characteristics and make the people wearing them look alike. The issue of stereotypes is very complicated, and it is sometimes hard because it changes how society views something, which sometimes is not the truth. Lamb to the Slaughter by Roald Dahl delivers a story of a housewife who kills her husband with a frozen lamb tight. What the husband and the wife do in this short story break the gender roles stereotypes labelled by the society. This article will analyse how the stereotypes are broken.Keywords: gender roles, society, stereotypes